1999
DOI: 10.1164/ajrccm.159.6.9808049
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Acquired in the Community Through Drug-Resistant Streptococcus pneumoniae

Abstract: The aim of the study was to determine the incidence of and risk factors for drug resistance of Streptococcus pneumoniae, and its impact on the outcome among hospitalized patients of pneumococcal pneumonia acquired in the community. Consecutive patients with culture-proven pneumococcal pneumonia were prospectively studied with regard to the incidence of pneumococcal drug resistance, potential risk factors, and in-hospital outcome variables. A total of 101 patients were studied. Drug resistance to penicillin, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
4
8

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 21 publications
7
78
4
8
Order By: Relevance
“…Between January 2000-April 2001, consecutive adults (o18 yrs) diagnosed with CAP and admitted to Hospital Clinic Institut d9Investigacions Biomèdiques August Pi i Sunyer (Universitat de Barcelona, Barcelona, Spain) were prospectively studied. CAP was defined as the presence of symptoms of a lower respiratory tract infection, combined with a new infiltrate on chest radiography, no emerging alternative diagnosis during follow-up and nonhospitalisation of the patient in the preceding 72 h. Clinical, radiographic, and laboratory data were recorded and entered into a computer database as described elsewhere [2,5].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between January 2000-April 2001, consecutive adults (o18 yrs) diagnosed with CAP and admitted to Hospital Clinic Institut d9Investigacions Biomèdiques August Pi i Sunyer (Universitat de Barcelona, Barcelona, Spain) were prospectively studied. CAP was defined as the presence of symptoms of a lower respiratory tract infection, combined with a new infiltrate on chest radiography, no emerging alternative diagnosis during follow-up and nonhospitalisation of the patient in the preceding 72 h. Clinical, radiographic, and laboratory data were recorded and entered into a computer database as described elsewhere [2,5].…”
Section: Patientsmentioning
confidence: 99%
“…Recent studies have suggested that S. pneumoniae may be underdiagnosed and that it may be responsible for at least one of three episodes of CAP without aetiological diagnosis [3,4]. The lack of rapid and sensitive diagnostic methods for determining pneumococcal aetiology, the high mortality associated with pneumococcal CAP and the emerging antibiotic resistance in strains of S. pneumoniae, justify the need to improve the diagnosis of potential pneumococcal aetiology of CAP [5][6][7].…”
mentioning
confidence: 99%
“…NUERMBERGER and BISHAI [8] discussed the uncertainties of the efficacy of macrolides against MRSP. EWIG et al [9] looked at patients hospitalised for community-acquired pneumococcal pneumonia and reported that there was no significant difference in mortality rate between patients infected with macrolide-susceptible versus macrolide-non-susceptible S. pneumoniae (12% versus 7%, respectively). ANZUETO et al [10] also reported that clarithromycin (CLR) had a good effect in the treatment of outpatients with acute exacerbations of chronic bronchitis caused by CLR-resistant pneumococci.…”
mentioning
confidence: 99%
“…Some studies have suggested that antibiotic resistance in S. pneumoniae is not clinically relevant [1][2][3], whereas others [4] have reported higher mortality rates among patients infected with nonsusceptible strains to the administered antibiotics. In a recent study by LUJAN et al [4], it was observed that receiving DAT, as a result of an invasive infection with resistant S. pneumoniae isolates, resulted in a significantly higher chance of mortality.…”
mentioning
confidence: 99%